1991
DOI: 10.1002/ajh.2830370204
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte proteases do not process endothelial cell‐derived unusually large von willebrand factor multimers to plasma vWF in vivo

Abstract: The unusually large von Willebrand factor (ULvWF) multimers present within endothelial cells and platelets are larger than the vWF multimers normally found in adult human plasma. Furthermore, ULvWF multimers are cleared rapidly from the circulation if they are released by intense endothelial cell stimulation. The mechanisms by which the ULvWF multimers are processed to large plasma vWF multimers are not known. It has been demonstrated that granulocyte proteases are capable of decreasing vWF multimer size in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…After depletion of neutrophils in ADAMTS-13 )/) mice, we did not observe a change in VWF multimer composition or satellite band appearance (not shown), suggesting that circulating neutrophils do not play a major role in regulating VWF size distribution, at least under normal, nonactivating conditions. These results are in accordance with the normal VWF size distribution observed in neutropenic patients [10]. Whether proteases from activated neutrophils could play a physiological role in VWF cleavage remains to be determined.…”
Section: In Vivo Vonsupporting
confidence: 89%
“…After depletion of neutrophils in ADAMTS-13 )/) mice, we did not observe a change in VWF multimer composition or satellite band appearance (not shown), suggesting that circulating neutrophils do not play a major role in regulating VWF size distribution, at least under normal, nonactivating conditions. These results are in accordance with the normal VWF size distribution observed in neutropenic patients [10]. Whether proteases from activated neutrophils could play a physiological role in VWF cleavage remains to be determined.…”
Section: In Vivo Vonsupporting
confidence: 89%
“…39,40 In a study of plasma VWF multimer patterns in patients with high or low neutrophil counts, 7 of 10 patients who exhibited decreased VWF multimer sizes had very high neutrophil counts, suggesting that high neutrophil counts were associated with increased VWF proteolysis. 41 Disseminated intravascular coagulation is associated with severe secondary deficiency of ADAMTS13 activity and might be expected to be accompanied by unusually large VWF multimers. 42 However, no significant correlation between ADAMTS13 deficiency and the presence of unusually large VWF multimers has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structure analysis has revealed that the cleavage sites are located in a β sheet that is loosely packed in the core of the A2 domain [83]. Since profound leucopenia is not accompanied by evidence of VWF size change, it is questionable that leukocyte proteases are involved in the regulation of VWF activity [84]. …”
Section: Adamts13 Is a Vwf Cleaving Metalloproteasementioning
confidence: 99%